Casa Familiar Rural do Vale do Jaguari: elementos formativos do território - Zimmermann, Angelita (2014)
In recent years the organization of rural workers have built public policies for Rural Education, held in recognition of the reality of workers in the field who have resisted to continue producing his life in rural areas, a dispute with the country's political projects whose design, development through agribusiness. This study aims to discuss the elements of a formative experience in Field Education: the process of implementation of the Rural Family House Valley Jaguari - CFRVJ. Located in the central region of Rio Grande do Sul, the CFR that covers the municipalities of Jaguari, Mata, Santiago and surrounding counties. Based in the Pedagogy of Alternation, is demonstrated as an educational proposal, able to meet the social demands of this group that has historically been subjected to educational processes that do not effectively meet their social needs. This study was a qualitative study, by participant observation, based on theoretical Rural Youth / Field, of Field Education and Planning. It is understood that the formative elements of construction emerged that territory, are constitutive of omnilateral training and explanation of the contradictions of the capitalist system. From the perspective of the rural youth through education field, based on the Pedagogy of Alternation, built, conceived and gestated by the Association CFRVJ a collective educational process, to integrate several social actors and local institutions, encourages a dialectic relationship building knowledge, strengthens social relations, constituting a new territory. In this process, it is believed that the CFRVJ could be a proposal for strengthening the Rural Education.